Pengaruh Persepsi Keadillan Gaji dan Job Insecurity Terhadap Turnover Intention Pada Karyawan PT Berkah Karpindo Group - Ria Aprilia; Sulistiyani Sulistiyani; Honorata Ratnawati Dwi Putranti; Syahtri Wardana Priyambodo (Lembaga Komunitas Informasi Teknologi Aceh (KITA), Indonesia, 2026)
This study aims to analyze the effect of perceived pay fairness and job insecurity on employee turnover intention at PT Berkah Karpindo Group, a project-based construction services company. The high rate of employee turnover in project-based organizations indicates problems related to the compensation system and the low level of perceived job security among employees. This study adopts a quantitative approach using a survey method. Data were collected through a five-point Likert scale questionnaire distributed to all 104 active employees using a census sampling technique. Data analysis was conducted using multiple linear regression. The results indicate that perceived pay fairness has a negative and significant effect on turnover intention, while job insecurity has a positive and significant effect on turnover intention. Simultaneously, perceived pay fairness and job insecurity jointly exert a significant influence on turnover intention, accounting for 43.4 percent of its variance. These findings demonstrate that compensation fairness and job security play an important role in reducing employees’ intention to leave in project-based organizations. Therefore, the results of this study are expected to serve as a basis for formulating human resource management policies aimed at improving employee stability and retention.